Aerobic and anaerobic biodegradation of BDE-47 by bacteria isolated from an e-waste-contaminated site and the effect of various additives - Huo, Lili; Zhao, Chenghao; Gu, Tianyuan; Yan, Ming; Zhong, Hua (Chemosphere (Oxford), 2022)
Degradation experiments are conducted to specifically compare the degradation of 2,2′,4,4′-tetrabromodiphenyl ether (BDE-47) by aerobic and anaerobic strains isolated from real e-waste sites contaminated by BDE-47. The effect of carbon sources, inducers and surfactants on the degradation was examined to strengthen such a comparison. An aerobic strain, B. cereus S1, and an anaerobic strain, A. faecalis S4, were obtained. The results indicated that BDE-47 could be used as the sole carbon source by B. cereus S1 and A. faecalis S4 under aerobic and anaerobic conditions, respectively. The degradation of BDE-47 by B. cereus S1 and A. faecalis S4 was illustrated a first-order kinetics process obtaining a removal efficiency of 61.6% and 51.6% with a first-order rate constant of 0.0728 d−1 and 0.0514 d−1, and corresponding half-life of 8.7 d and 13.5 d, respectively. The addition of carbon sources (yeast extract, glucose, acetic acid and ethanol) and inducers (2,4-dichlorophenol, bisphenol A and toluene) promoted BDE-47 degradation by both B. cereus S1 and A. faecalis S4 under aerobic and anaerobic conditions, while hydroquinone as the inducer inhibited the degradation. All of the surfactants tested (CTAB, Tween 80, Triton X-100, rhamnolipid and SDS) showed inhibitory effect. BDE-47 degradation by B. cereus S1 under aerobic condition was more efficient than A. faecalis S4 under anaerobic condition whether with or without the additives. The results of the study indicated that in the field sites contaminated by BDE-47, the aerobic condition can be more favorable for BDE-47 removal and the degradation can be further enhanced by applying suitable carbon sources and inducers. [Display omitted] •Aerobic and anaerobic BDE-47 degradation strains were isolated from real e-waste sites.•The isolated B. cereus and A. faecalis degraded BDE-47 as the sole carbon source.•Aerobic condition was more favorable than anaerobic for BDE-47 degradation.•Carbon sources and inducers promoted BDE-47 degradation and surfactants inhibited.